Lightning risk assessment for hall building based on Malaysian standard MS IEC / Mohd Amzar M. Amin - M. Amin, Mohd Amzar (2013)
This thesis analyses the lightning risk assessment for structure concept. After a brief introduction to lightning, lightning discharge process and the consequences of a lightning strike, the Malaysian standards for the protection of structures against lightning are analyzed and compared in the scope of requirement for the lightning protection. Malaysian standards assesses risks of lightning strike to Examination Hall which is Dewan Sri Budiman UiTM Shah Alam, Malaysia for the application of the new Malaysian standards for reference. It carries out data collection and zoning on the hall as well as the lightning risk assessment according to the evaluation process and method. The thesis seeks to compare all the achievement Lightning risk values with reference value results of the assessment. Finally it makes the recommendation needed with lightning protection of hall building.